MORAL REASONING MEMEDIASI LOVE OF MONEY DAN TAX EVASION UMKM - Silmi, Silmi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to analyze the effect of love of money on tax evasion with moral reasoning as a mediating variable among Micro, Small, and Medium Enterprises (MSMEs) taxpayers in West Sumatra Province. The research employed a quantitative explanatory approach with purposive sampling. A total of 100 respondents who possessed active taxpayer identification numbers (NPWP) and had submitted annual tax returns for at least the last two years were selected as samples. Data were collected using a five-point Likert scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that love of money has a significant positive effect on tax evasion and a significant negative effect on moral reasoning. Furthermore, moral reasoning has a significant negative effect on tax evasion. The mediation test indicates that moral reasoning partially mediates the relationship between love of money and tax evasion. These findings suggest that a high materialistic orientation increases the tendency to evade taxes; however, this effect can be mitigated through strengthened moral reasoning.Keywords: love of money, moral reasoning, tax evasion, MSMEs, PLS-SEM